2014
DOI: 10.1149/2.0111503jes
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the NADH Cofactor by a Rhodium Complex Immobilized on Multi-Walled Carbon Nanotubes

Abstract: The regeneration of the enzymatic cofactor nicotinamide adenine dinucleotide (NADH) by rhodium-based catalysts such as [Rh(Cp * )(bpy)Cl] + (Cp * = pentamethylcyclopentadienyl, bpy = 2,2 -bipyridine) and derivatives have previously been studied extensively in solution. In this work, we report a synthetic route of a rhodium complex with a pyrene-substituted phenanthroline ligand (pyr-Rh). The immobilization of the pyr-Rh complex was accomplished on multi-walled carbon nanotubes (MWCNTs) via π-π stacking to obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 50 publications
1
43
1
1
Order By: Relevance
“…Most commonly, CO 2 reduction has been explored with the aim of producing formate or alkanes/alcohols, although NAD þ reduction to NADH is frequently attempted where NAD-dependent enzymes can support reductive reactions [22][23][24]; Vincent and co-workers [25] have also demonstrated that the coimmobilization of hydrogenase and NAD þ -reducing proteins onto conductive particles can facilitate H 2 -driven NADH production. Recent research has also explored the possibility of reducing dinitrogen (N 2 ) to an important chemical commodity, ammonia (NH 3 ), while simultaneously producing electrical energy [26].…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, CO 2 reduction has been explored with the aim of producing formate or alkanes/alcohols, although NAD þ reduction to NADH is frequently attempted where NAD-dependent enzymes can support reductive reactions [22][23][24]; Vincent and co-workers [25] have also demonstrated that the coimmobilization of hydrogenase and NAD þ -reducing proteins onto conductive particles can facilitate H 2 -driven NADH production. Recent research has also explored the possibility of reducing dinitrogen (N 2 ) to an important chemical commodity, ammonia (NH 3 ), while simultaneously producing electrical energy [26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reportedt hat the combination of the three NADH-dependent enzymes, formate dehydrogenase (FDH), formaldehyde dehydrogenase (FLDH), and alcohol dehydrogenase (ADH) enables the production of methanol from CO 2 in am etabolically reversedr eactionc ascade. [33] To increaset he efficiency of this cascade, efforts have been made to drive the equilibrium toward CO 2 reduction using electrochemical NADH regeneration systems. [34] Lee and colleagues have screened the various protein homologs to determinet he variants with the highest activities in the reductive direction; [35] the results of this work are certaint oi nform further efforts involving this enzyme cascade.…”
Section: Co 2 Reduction To Comentioning
confidence: 99%
“…One strategy employed to overcome these difficulties (fouling and overvoltage and side reactions) was the use of mediator-modified electrodes, where the mediators are used to shuttle electrons from NADH to the electrode surface and allow electron transport between them [5,[9][10][11][12][13][14][15][16]. Some mediators (electrocatalysts) were immobilized on the electrode surface by covalent attachment, electrochemical polymerization, incorporation in carbon paste, adsorption, self-assembly and via entrapment in polymeric matrices [4,[17][18][19]. Another strategy is modification of the electrode surface with a polymeric substance, using electrodes modified with carbon nanotubes, nanofibers or using enzymatic methods that follow bioelectrocatalytic reaction [2,4,13,15,16,[20][21][22][23].…”
Section: David Publishingmentioning
confidence: 99%